Analysis of Water Quality in Pangeranan Estuari, Bangkalan, Madura Using the Pollution Index and Storet Methods - Arrayanul Jannah, Annisa; Mertiara Ratih Terry Laksani; Zainuri, Muhammad; Farid, Akhmad (Journal of Marine and Coastal Science, 2025)
The extensive use of estuaries makes them vulnerable to being used as dumping sites for waste from human activities. Continuous accumulation of rubbish in estuaries can cause water pollution and decrease water quality. Pangeranan Waters is one of the estuari waters in Bangkalan Regency, East Java which is widely used by the community. Therefore, the aim of this research is to determine the water quality of the Pangeran Bangkalan Madura River estuari using two different methods. This research was conducted in November 2024 by collecting in-situ and ex-situ data at low and high tide. The results of water quality measurements are then analyzed to determine its status using two methods, namely Pollution Index and Storet. From this analysis, the water quality status was Pollution Index obtained as follows: at low tide, it shows a moderate level of pollution, while at high tide and highest tide, the status shows heavy pollution. The results of analysis using the Storet method show that the average physical parameter skorat stations 1 to 5 is -9, which is in the lightly polluted category. Meanwhile, for chemical parameters, the average skorobtained was -60, which is classified as heavily polluted.